Pengaruh Penggunaan Infra Red di Posyandu Lansia Desa Lama - Sulaiman Sulaiman; Anggriani Anggriani (Pelita Masyarakat, 2019)
The elderly Posyandu is a form of health service from the community of Lama Village, Pancur Batu District, in providing basic services specifically for the elderly, their rights in health services can be fulfilled. Population aged 60 years and over as many as 120 people, the average elderly are looking for physical care and better. The purpose of this service is to provide information on the use of infrared light for cadres, elderly families and the elderly. In this service the method used is to do counseling, training in the use of infrared for the age, cadres and families who take part in community service. The health level of the elderly is increasing, cadres and elderly families understand how to use infra red. Provision of infrared light has a very significant impact in improving health status in Lama Village, Pancur Batu District.